Memaksimalisasi Keuntungan Pada Warung “Mie Ayam Mas Tri” Dengan Menggunakan Metode Simpleks - Anistasah, Cindy; Kurnia, Ega; Sukani, Sri Rejeki; Ananta, Yuli Dhea; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
The aim of this research is to find out whether the combination of inputs used to produce a product in the form of chicken noodles is an optimal combination and whether the resulting product can provide maximum profits. To find out the maximum combination of input and profit, the simplex method can be used. From the research results it is known that the optimal combination of inputs can provide profits of IDR. 1,652,000.00-.